2017
DOI: 10.1159/000484232
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Positive Feedback Loop Between NTSR1 and Wnt/β-Catenin Contributes to Tumor Growth of Glioblastoma

Abstract: Background/Aims: Neurotensin (NTS), an intestinal hormone, is profoundly implicated in cancer progression through binding its primary receptor NTSR1. The conserved Wnt/β-Catenin pathway regulates cell proliferation and differentiation via activation of the β-catenin/T-cell factor (TCF) complex and subsequent modulation of a set of target genes. In this study, we aimed to uncover the potential connection between NTS/NTSR1 signaling and Wnt/β-Catenin pathway. Methods: Genetic silencing, pharmacological inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…NT has been shown to activate NF‐κB signaling pathways 97 ; however, we show that NT negatively regulates α‐defensin gene expression and NF‐κB signaling in Paneth cells in the current study. In order to better understand the contradiction of our results with previous reports, we found that PKCτ negatively regulates NF‐κB signaling.…”
Section: Discussioncontrasting
confidence: 87%
“…NT has been shown to activate NF‐κB signaling pathways 97 ; however, we show that NT negatively regulates α‐defensin gene expression and NF‐κB signaling in Paneth cells in the current study. In order to better understand the contradiction of our results with previous reports, we found that PKCτ negatively regulates NF‐κB signaling.…”
Section: Discussioncontrasting
confidence: 87%
“…The unexpected observation during experimentation of NTSR1 knockdown being associated with a more epithelial phenotype while knockdown of NTSR3 resembled a more mesenchymal phenotype, is unique. Indeed, similar plasticity regarding epithelial and mesenchymal states in OvCa cells has been reported and a role for NTS signaling, primarily acting through the NTSR1 receptor, in EMT has been described in several cancers . Thus, because epithelial cells are more proliferative and exhibit greater collective cell migration, it is possible that the effects of NTSR1 knockdown reflect the shift in EMT state.…”
Section: Discussionmentioning
confidence: 61%
“…Dose and duration were selected according to previously published studies. 20 , 21 , 22 , 23 After 21 days, the animals were sacrificed, and kidneys were collected for the assessment of kidney fibrosis.…”
Section: Methodsmentioning
confidence: 99%